ANALYSIS OF FACTORS AFFECTING BEHAVIORAL INTENTION OF NURSING STUDENT AS BYSTANDER CARDIOPULMONARY RESUSCITATION (CPR) ON HANDLING OUT OF HOSPITAL CARDIAC ARREST (OHCA) IN MALANG - Suis Galischa Wati; Titin Andri Wihastuti; Tina Handayani Nasution (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2017)
The incident of Out of Hospital Cardiac Arrest (OHCA) increased every year. One of effort to enhance survival rate due to the incident is by increasing the number of bystander CPR. Besides of a good knowledge and skill about CPR, the tendency of someone for willing or unwilling to behave as a bystander CPR is strongly influenced by their behavioral intention. The aims of this research was to analyze various factors that influence behavioral intention of nursing students to become a bystander CPR. This was a cross-sectional study with proportional sampling tecnique. As a sample of this study were 108 students from various nursing institution in Malang. Multivariat analysis with logistic regression was used to identify the most dominant factor which influencing behavioral intention. Logistic regression showed the following result: age p=0,341, OR=1,683; gender p=0,022, OR=3,113; CPR experience=0,327, OR=1,808 and knowledge: p=0,007, OR=3,101. The result of this study conclude that knowledge about CPR is the most dominant predictor factor in influencing behavioral intention.